Better safe than sorry: Toxic waste management after unionization - Magnus Schauf; Eline Schoonjans (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2022)
Do unions protect workers from releasing or handling toxic waste? This paper studies the impact of organized labor on toxic waste management at US facilities between 1991 and 2020. If unions, as collective voice, bargain for worker benefits such as workplace safety and member health, their effect on toxic releases remains unclear due to a tradeoff. Reducing toxic waste releases has positive health and environmental effects but requires more and dangerous activities to handle waste after production. Using a regression discontinuity design on close-call union elections, we find a significantly negative effect of unionization on the sum of toxic waste recycling, energy recovery, and treatment at the facility site. In contrast, total toxic releases to air, land, and water increase after unionization. These effects are more pronounced in states without right-to-work laws, for less toxic chemicals, and for non-heavy industries. Finally, we show that unionized facilities increase waste prevention activities through innovative product and process modifications and have less catastrophic releases. However, these effects cannot offset the reduction in waste handling, resulting in more waste releases. Our findings suggest that unions prioritize safety over sustainability and call upon managerial and governmental action to better align these two objectives.
Keywords: 330